MODERN CONCEPTS AND STAGES OF RISK MANAGEMENT AT UNIVERSITIES (Education in the 21st Century, 2023)
For any organization, even in favorable economic conditions, the possibility of crisis phenomena always remains. Such phenomena contribute to the occurrence of risks. Risk is inherent in any field of human activity, it is associated with many conditions and factors affecting the outcome of decisions. Historical experience shows that the risk of not achieving the planned results began to manifest itself especially in the modern economic system.Current issues and trends in risk management continue to attract the attention of local researchers and entrepreneurs. The presence of risk is, in fact, a key aspect of economic freedom. Since the state regulation in market conditions is mainly expressed by the implementation of business activities and setting standards for tax collection, everything else is determined by the producer and the consumer, at their will. In a market economy, the profit of some may turn into a loss for others, and "equal economic freedom of market subjects inevitably causes economic risk".This article demonstrates and proves that the consideration of many tasks with the scale of risk assessment allows to get the maximum insight and to more accurately understand the importance of external and internal factors affecting universities, their interaction and thus the stages of effective risk management are introduced.The novelty of the research is the modern concepts and stages of risk management at universities, which can represent practical value, taking into account the fact that the stages of risk management of universities is not developed in the context of higher education.Thus, risks are inherent in any type of human activity, their presence does not depend on the conscious efforts of individuals. In addition, they are continuous and all economic entities are affected by them, regardless of their status. In other words, selectivity is not intrinsic to risk at all. The universality of risks is an abstract and concrete possibility.
Keywords: possibility of risks; risk management; stages of risk management; inconsistency; alternativeness; uncertainty